The optimization of the basis for the social insurance contribution rates for individuals operating a business enterprise on their own pursuant to provisions applicable to business activities - Krajewski, Marcin (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The article presents methods of optimizing the basis for the social insurance contribution rates for individuals operating a business enterprise on their own pursuant to provisions applicable to business activities. The consequences of applying optimization are also analyzed, both from the point of view of the insured person, the income of the Social Insurance Fund and the impact of optimization on the labor market. A person starting a non-agricultural business activity may pay lower contributions for up to sixty-six months. Such a long period of preference applied by the legislator causes short-term benefits in the form of lower operating costs, but in the future it will lower the level of pension and disability benefits.